2003
DOI: 10.1051/0004-6361:20021737
|View full text |Cite
|
Sign up to set email alerts
|

A study of coronal abundances in RS CVn binaries

Abstract: Abstract. We present XMM-Newton data of several RS CVn binary systems. High-resolution X-ray spectra obtained with the Reflection Grating Spectrometers have been interpreted simultaneously with the European Photon Imaging Camera spectra. Highly active stars show a depletion of elements with a low first ionization potential (FIP) relative to high-FIP elements, whereas intermediately active binaries show either no FIP bias or a possible solar-like FIP effect. We find that the low-FIP abundance ratios to oxygen v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
129
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(146 citation statements)
references
References 68 publications
(99 reference statements)
14
129
3
Order By: Relevance
“…AB Dor and V471 Tau clearly share similarities in coronal composition: both show the same general pattern characterized by a depletion of low-FIP elements by a factor of $3, evidence for slightly smaller depletions of intermediate-FIP elements S and O, and a clear enhancement of Ne relative to elements of lower FIP. This pattern is similar to, although less extreme than, those seen in other active stars and RS CVn-type binaries (see, e.g., reviews by Drake 2003a; Audard et al 2003). That the abundances found here represent real metal depletions in the coronae of both AB Dor and V471 Tau is beyond doubt.…”
Section: Coronal Abundancessupporting
confidence: 88%
See 2 more Smart Citations
“…AB Dor and V471 Tau clearly share similarities in coronal composition: both show the same general pattern characterized by a depletion of low-FIP elements by a factor of $3, evidence for slightly smaller depletions of intermediate-FIP elements S and O, and a clear enhancement of Ne relative to elements of lower FIP. This pattern is similar to, although less extreme than, those seen in other active stars and RS CVn-type binaries (see, e.g., reviews by Drake 2003a; Audard et al 2003). That the abundances found here represent real metal depletions in the coronae of both AB Dor and V471 Tau is beyond doubt.…”
Section: Coronal Abundancessupporting
confidence: 88%
“…Studies of solar-like active stars confirm the suspicions engendered by earlier work (e.g., Drake et al 1996 and references therein) that a transition from a metaldepleted to a metal-rich corona occurs as the activity decreases (Güdel et al 2002); this is now better characterized as a change from an apparently ''inverse FIP effect'' to a FIP effect. Audard et al (2003) showed a similar transitions from an inverse FIP effect to the absence of an obvious FIP effect for RS CVn binary stars with decreasing activity. Only one star studied in detail to date on the basis of high-resolution spectra appears to have a coronal composition demonstrably similar to that of its underlying photosphere: the subgiant Procyon (F5 IV; Drake et al 1995;Raassen et al 2002).…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…5, EI Eri shows the typical inverse FIP effect observed in the most active coronae (Brinkman et al 2001;Audard et al 2003). In particular, the Ne abundance is enriched by a factor ∼3 compared to Fe, and a lesser enrichment is observed for C, N, and O (all high FIP) over Fe (low FIP), The abundance ratio of the low-FIP elements Mg and Si to Fe is approximately solar, although with respect to H, they are all subsolar (∼0.3).…”
Section: A22 Page 4 Ofmentioning
confidence: 97%
“…In some cases, the high-FIP elements are even enriched compared to the low-FIP ones, an effect labeled the inverse-FIP (IFIP) effect (Brinkman et al 2001). Later studies revealed that FIP and IFIP biases are correlated with coronal activity (and age): Highly active stars show an IFIP effect, while less active coronae have a solar FIP bias (Audard et al 2003;Telleschi et al 2005), implying a transition on stellar-evolution time scales of Gyr. A&A 550, A22 (2013) On the face of it, the correlation with activity supported previous suggestions that abundances may be linked to flares (e.g., Güdel et al 1999Güdel et al , 2004Osten et al 2003;Nordon et al 2006).…”
Section: Introductionmentioning
confidence: 99%